Pengaruh Orientasi Kewirausahaan Terhadap Kinerja Produk Pada Agroindustri Kopi di Kota Bukittinggi - Afrianingsih Putri; Rika Hariance; Nofialdi Nofialdi (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2017)
Putri et al, 2017. The Effect of Entrepreneurship Orientation onÂ Product Performance of Coffee Agroindustry in Bukittinggi. JLSO 6(1):1-6.Succes of business development determined by the entrepreneur ability to develop ideas and search for business opportunities. Creativity in developing ideas is one of the most quality an entrepreneur should have in order to achieve business success. Entrepeneur can be achieve the quality if the have a clear orientation toward product and market. The purpose of this study is to detemermine the effect of entrepreneurship orientation on product performance of coffee agroindustry in Bukit tinggi. Sample for this study was token randomly as much as 30 coffee agroindustry in city of Bukit tinggi. The data were analized using regression analysis with independent variables of entrepreneurship orientation while the dependent variable was product performance. The result shows that variables include entrepreneurship orientation : goal, product creation, innovation and risk simultaneously affect the product performance. However, partially only innovation ability affect the product performance.